Democratization and its Balance Sheet in Francophone and Anglophone Africa; the Zambian and Beninese Experience - Mbihbiih, Niying Roger (American Scientific Research Journal for Engineering, Technology, and Sciences, 2014)
While no two democratization processes unraveled along the same lines, broad patterns of social mobilization and democratic transition are easily discernable across sub Saharan Africa in the wake of the pro-democracy movements of the 1990’s. Even though scholarship on this process has received its fair share of investigative enquiry from multi-dimensional perspectives, the direction adopted here intends to present a comparative analysis of democratization dynamics in Benin and Zambia-the pioneers of democratization in Francophone and Anglophone sub-Saharan Africa respectively. Constitutional engineering, Sovereign National Councils (SNC), and other mechanisms of citizen participation characterized the transition process in these two case studies with the implication that a split had been orchestrated with the old order. The new regimes whose ideologies appealed to the masses in the newly revitalized political space assumed political power on the premise that a new social contract anchored along certain socio-economic and political prerequisites would be fulfilled to the satisfaction of the latter. Cognizance of the progress recorded in both Zambia and Benin in the post 1990 democratization era, it becomes imperative to highlight the progress and hiccups that this movement has encountered in its drive to democratic consolidation.